Phylogenetic analyses allow species-level recognition of Leptographium wageneri varieties that cause black stain root disease of conifers in western North America - Choi, Daram; Harrington, Thomas C.; Shaw, David C.; Stewart, Jane E.; Klopfenstein, Ned B.; Kroese, Duncan R.; Kim, Mee-Sook (Frontiers in Plant Science, 2023)
Leptographium wageneri is a native fungal pathogen in western North America that causes black stain root disease (BSRD) of conifers. Three host-specialized varieties of this pathogen were previously described: L. wageneri var. wageneri on pinyon pines (Pinus monophylla and P. edulis); L. wageneri var. ponderosum, primarily on hard pines (e.g., P. ponderosa, P. jeffreyi); and L. wageneri var. pseudotsugae on Douglas-fir (Pseudotsuga menziesii). Morphological, physiological and ecological differences among the three pathogen varieties have been previously determined; however, DNA-based characterization and analyses are needed to determine the genetic relationships among these varieties. The objective of this study was to use DNA sequences of 10 gene regions to assess phylogenetic relationships among L. wageneri isolates collected from different hosts. The multigene phylogenetic analyses, based on maximum likelihood and Bayesian inference, strongly supported species-level separation of the three L. wageneri varieties. These results, in conjunction with previously established phenotypic differences, support the elevation of L. wageneri var. ponderosum and L. wageneri var. pseudotsugae to the species level as L. ponderosum comb. nov. and L. pseudotsugae comb. nov., respectively, maintaining L. wageneri var. wageneri as Leptographium wageneri. Characterization of the three Leptographium species, each with distinct host ranges, provides a baseline to further understand the ecological interactions and evolutionary relationships of these forest pathogens, which informs management of black stain root disease.